Hubungan Perkembangan Menggambar Bebas dengan Kemampuan Berhitung Anak di Taman Kanak-kanak - Lourena, Dian; Mayar, Farida (ARZUSIN, 2024)
The background of the issue in the study is that cognitive abilities of children are still underdeveloped. Especially in children's arithmetic abilities when doing free drawing activity. This research objective is to see the relationship between the development of free drawing and children's arithmetic abilities. Therefore, the issue that will be examined in this research is "The Relationship Between the Development of Free Drawing and Children's Arithmetic Ability in Kindergarten". The type of this research is quantitative research by utilizing the correlation method. This correlation method aims to reveal whether there is a relationship between two different variables or not. The technique of data analysis in this research utilizes simple regression, and in data collection using a questionnaire distribution using a Likert scale. The first variable (X) is free drawing, the second variable (Y) is children's arithmetic ability. This research was carried out in a kindergarten in Guguak District, Lima Puluh Kota Regency with 15 teachers as respondents. In order to test the hypotheses, the study employed the use of t-test statistics, with a significance level of 5% (=0.05). The findings of the study indicated that in the calculation found the value of F count 49.43> Ftable 4.67, then it has been deduced that there is a relationship between Free Drawing of Early Childhood (X) and Children's Arithmetic Ability (Y) in Kindergarten.